Tumia Mbegu Bora za Viazi Vitamu: Ongeza Mavuno... Ongeza Mapato - International Potato Center; Busoga Commercial Seed Producers and Marketing Cooperative Society (2025)
This Kiswahili-language poster encourages farmers in Tanzania and East Africa to adopt certified sweetpotato seed for higher productivity and income. Based on field experiments by BUSECO and the International Potato Center (CIP), certified vines provided up to 142% higher yields compared to farmer-recycled seed. The poster includes comparative photos showing bigger roots and greener, healthier plants from certified vines, along with contact information for certified seed suppliers. It promotes the slogan “Vuna Mafanikio” (“Harvest Success”) to motivate investment in quality planting materials.